Are corporate biodiversity commitments consistent with delivering 'nature-positive' outcomes? A review of 'nature-positive' definitions, company progress and challenges. (15th December 2022) - zu Ermgassen, Sophus O.S.E.; Howard, Michael; Bennun, Leon; Addison, Prue F.E.; Bull, Joseph W.; Loveridge, Robin; Pollard, Edward; Starkey, Malcolm
Abstract: There are growing calls for businesses to implement 'nature-positive' strategies. Convergence around a precise definition is now needed. We review definitions of 'nature-positive', highlight differences between 'nature-positive' and previous iterations of organizational biodiversity strategies (e.g. net positive impact) and propose four key elements for 'nature-positive' strategies: 1) demonstrating positive biodiversity outcomes across the entire value chain ("scope"); 2) buy-in throughout the entire organization ("mainstreaming"); 3) integrated consideration of different components of nature (e.g. both biodiversity and climate; "integration"); and 4) measurable outcomes against a fixed baseline aligned with overall societal goals (e.g. post-2020 Global Biodiversity Framework; "ambition"). We analyse trends in biodiversity commitments of the Global Fortune 100 companies and firms that have made recent 'net impact' commitments, evaluating alignment with these elements and where possible assessing their evolution since 2016. Uptake of biodiversity commitments has increased since 2016, but with limited progress towards adopting measurable, time-bound commitments (an increase from 5 to 10/100 Fortune 100 firms from 2016 to 2021). We review barriers to business implementation of strategies that can deliver socially equitable and 'nature-positive' outcomes. Major improvements are needed in data availability and transparency, regulation and sector-wide coordination that creates level playing fields and prevents impact leakage. Transformative action is required to create production and consumption systems that actively enhance nature.